Breast Feeding Practices Up To 6 Months In Infants Of Urban Area : A Hospital Based Survey (Indian Journal of Applied-Basic Medical Sciences, 2020)
Introduction : Adopting optimal breast feeding practices is fundamental right to a child’s survival, growth  and development. Despite all the potential benefits, only about two fifths of infants 0-6 months of age worldwide are exclusively breastfed. Analysis of data on feeding practices  among infants highlights the need for accelerated programming in this area. Present study  was aimed to survey feeding practices in infants up to 6 months and observing variables for  faulty feeding practices Method :Mother of infants up to 6 months coming from urban area in a tertiary care hospital were  interviewed for feeding practices as per preformed questionnaires. If feeding practices were  faulty all details regarding various factors leading to same were asked and analysed. Results :Total 518 mothers were interviewed. Only 37% infants were exclusively breast feed, in 29%  feeding was started in 1st hour of life and in 25% some form of prelacteal feeds were given.  On analysing different factors for faulty feeding practices we found that primigravida, CS  delivery, (p
Keywords: Exclusively breast feed; Breast feeding practices up to 6 months in infants of urban area; A hospital based survey